Improving English Vocabulary on Things Around Us Using Matching Pairs Game for The Seventh Grade Students of SMP Negeri 2 Jatinom in 2025 (JMKSP (Jurnal Manajemen, Kepemimpinan, dan Supervisi Pendidikan), 2025)
This Classroom Action Research (CAR) aimed to investigate whether the Matching Pairs Game could be used to improve the vocabulary mastery of seventh-grade students at SMP Negeri 2 Jatinom on the topic of "Things around Us." This study employs a mixed-methods approach to data analysis, aligning with the data collection methods used. The research indicator achievement is focused on students' mean scores, the findings consistently revealed a progressive achievement in value attainment as the intervention cycles were implemented. The initial data revealed a low baseline achievement, with the students' mean score (X) being only 51.8. After implementing the first intervention (Cycle 1), the mean score showed a significant rise to 61.8, indicating a positive effect, though still short of the success criteria. The teaching method was then refined, and the implementation in Cycle 2 resulted in a substantial increase, culminating in a final mean score of 80.8. This progressive and marked improvement from 51.8 to 80.8 confirms that the application of the Matching Pairs Game is highly effective. Therefore, the study concludes that the Matching Pairs Game is proven to be an effective strategy to improve the students' vocabulary mastery on the specified material.